Pengaruh Kepribadian Proaktif, Dukungan Keluarga dan Dukungan Universitas Terhadap Niat Kewirausahaan Pada Mahasiswa DIY Dengan Perceived Behavioral Control (PBC) Sebagai Variabel Moderasi - Shandhi Alamsyah; Al.Patriot Putera Mahendra; Edigar Filipe Pereira; Miswanto Miswanto; Baldric Siregar; Frasto Biyanto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study examines the factors that influence students' entrepreneurial interest in the Special Region of Yogyakarta (DIY), focusing on the impact of proactive personality, family support, and university support. In addition, the role of perceived behavioral control (PBC) as a moderator variable that reflects an individual's belief in their ability to carry out entrepreneurial activities is also examined. The urgency of this study is based on the high unemployment rate in Indonesia, which places entrepreneurship as an important strategy in creating jobs and strengthening the national economy. Theoretically, this study integrates the Theory of Planned Behavior (TPB) and Social Cognitive Theory (SCT). TPB explains that behavioral intentions are influenced by attitudes and subjective norms, while SCT highlights the importance of personal factors and environmental support in shaping behavior. This study uses a quantitative approach through a survey of 201 students from various universities in DIY, with a questionnaire instrument based on measurable indicators. Data analysis was carried out using Partial Least Squares Structural Equation Modeling (PLS-SEM) through SmartPLS 4.0 software. Validity and reliability tests showed strong results (Cronbach's alpha > 0.95; AVE > 0.83; HTMT < 0.90). The results showed that proactive personality (β = 0.318; p < 0.001), family support (β = 0.256; p < 0.001), and university support (β = 0.398; p < 0.001) had a significant positive effect on entrepreneurial interest. In addition, PBC was proven to moderate the relationship between the three variables on entrepreneurial interest, indicating that perceived self-control strengthens the influence of each independent variable. These findings emphasize the importance of developing proactive character and creating a supportive environment to encourage entrepreneurship among DIY students.